How much New is there in the Old? „Themis, Dike” and an Evolutionary Understanding of Ancient Greek Normativity - Skarbek-Kazanecki, Jan (Collectanea Philologica, 2025)
The study of normative and legal systems in archaic Greece reveals two competing interpretative models. The first highlights the autonomy of early lawmakers, portraying them as largely free from the constraints of inherited traditions and capable of enacting diverse laws and decrees. The second posits the existence of shared pan-Hellenic practices, a standardized legal terminology, and, above all, common cultural norms underlying the sanctions applied across various poleis. At the turn of the 19th and 20th centuries, these seemingly opposing perspectives were synthesized into a progressive interpretative framework. This new model presented the history of ancient Greece, starting in the early archaic period, in terms of tension and conflict between two normative systems, the old and the new – and, by extension, two contrasting approaches to the administration of communal justice. Importantly, the conceptual categories for these two historical “moments” were embodied in the terms themis and dike. The article offers a hermeneutic reconstruction of early 20th-century research on the themis–dike distinction, highlighting its influence on contemporary scholarship. It examines how these old assumptions and paradigms have shaped current interpretations of these foundational concepts.